Disease threshold for cherry leaf spot incidence on commercial sweet cherry cultivars - M. Varga; A. Vámos; B. Molnár; I. J. Holb (International Journal of Horticultural Science, 2019)
The aim of this study was to demonstrate the 10% threshold level for cherry leaf spot incidence on 23 commercial sweet cherry cultivars in two training systems. Twenty three cherry cultivars were evaluated in the two training systems with a spacing of 4 x 1 m and with a spacing of 2 x 5 m. Results showed that leaves of many cultivars were heavily infected, e.g. cultivars (cvs) ’Biggareau Burlat’, ’Sunburst’, while others showed low disease incidence e.g. cvs ’Celeste’ and ’Blaze Star’. According to the 10 % threshold level, cv ’Celeste’ proved to be the most resistant cultivar to leaf infection, while cv ’Münchebergi korai’ exceeded extremely the 10% threshold level. Leaf spot incidence was affected by training system on most cultivars. Thirteen cultivars had less than 10% infection in the 4 x 1 m spacing (i.e. they did not reach the 10% disease threshold level). At the same time, only 3 cultivars showed less than 10% infection in the 5 x 2 m spacing.